Expression of Autophagy-Related Factors LC3A and Beclin 1 and Apoptosis-Related Factors Bcl-2 and BAX in Osteoblasts Treated With Sodium Fluoride - Xu, Lin; Deng, Chaonan; Zhang, Ying; Zhao, Lina; Linghu, Yan; Yu, Yanni (Frontiers in Physiology, 2021)
Objective This study aims to analyze the expressions of autophagy-related factors light chain 3 alpha (LC3A) and Beclin 1 and apoptosis-related factors B-cell lymphoma 2 (Bcl-2) and Bcl-2-associated X (BAX) in primary osteoblasts treated with sodium fluoride (NaF). Methods Osteoblasts were extracted from Sprague-Dawley rats and treated with 0, 2.5, 5, and 10 mg/L NaF solutions, followed by 10 mmol/L 3-methyladenine (3-MA) for 24 h. The apoptotic rate was determined by flow cytometry, and the expressions of the autophagy- and apoptosis-related factors were measured by western blotting and real-time quantitative polymerase chain reaction. Results The mRNA expressions of LC3A, Beclin 1, and BAX in the NaF-treated osteoblast group were higher than those in the control group, while the protein expressions of these factors in the NaF-treated group were significantly higher than those in the control group. However, the Bcl-2 protein expression in the NaF-treated osteoblasts was significantly decreased compared to that in the control cells. After the 3-MA treatment, the protein expressions of LC3A, Beclin 1, and Bcl-2 were significantly decreased compared with those of the NaF-treated group, whereas the expression of BAX increased. Moreover, the apoptosis rate was increased after the addition of the 3-MA inhibitor. Conclusion NaF stimulation promoted autophagy and apoptosis of the osteoblasts, suggesting the involvement of fluoride damage in these processes.